Antioxidant and antiapoptotic effects of erdosteine in a rat model of ovarian ischemia-reperfusion injury - Ugurel, Vedat; Cicek, Ahmet Cagatay; Cemek, Mustafa; Demirtas, Selim; Kocaman, A. Tuba; Karaca, Turan (MASHHAD UNIV MED SCIENCES, 2017)
Objective(s): To evaluate the protective effect of erdosteine, an antiapoptotic and antioxidant agent, on torsion-detorsion evoked histopathological changes in experimental ovarian ischemia-reperfusion (IR) injury. Materials and Methods: Eighteen female Wistar albino rats were used in control, IR, and IR+Edosteine (IR-E) groups, (n=6 in each). The IR-E group received the erdosteine for seven days before the induction of torsion/retorsion, (10 mg/kg/days). The IR and IR-E groups were exposed to right unilateral adnexal torsion for 3 hr. Three hours later, re-laparotomy was performed, and the right ovaries were surgically excised. Oxidant and antioxidants levels were determined in serum. The ovarian tissue samples were received and fixed with 10% neutral buffered formalin. The sections were stained with H&E, anti-PCNA, and TUNEL. Results: The IR group were showed severe acute inflammation, polynuclear leukocytes and macrophages, stromal oedema and haemorrhage. Treatment with erdosteine in rats significantly retained degenerative changes in the ovary PCNA (+) cell numbers were significantly decreased in the IR and IR-E groups unlike the control group. However, its numbers were significantly increased in the IR-E group unlike the IR group. TUNEL (+) cell numbers were significantly increased in the IR group unlike the control and the IR-E groups. In erdosteine treated group, TUNEL (+) cells were detected significantly less than the IR group (P<0.05). Conclusion: In conclusion, erdosteine maybe a protective agent for ovarian damage and decreasing lipid peroxidation products and leukocytes aggregation after adnexal torsion in animals.
Keywords: Antioxidant; Erdosteine; Ischemia-reperfusion; Oxidant; Ovary; Rat; VITAMIN-E; HIND-LIMBS; COMBINATION; APOPTOSIS; DAMAGE; Research & Experimental Medicine; Pharmacology & Pharmacy